MENINGKATKAN MINAT BACA ANAK-ANAK DI DESA SILIWANGI - Slamet Riyadi; Bayu Saputra; Sintia Shafitri; Efi Yanti; Dina Cahya Anggraini; Rifki Ramadhani; Dea Larasati; Rahmi Rabila; Uswatun Khasanah Hutama; Lisa Pitriana (Journal of Pedagogi, 2024)
Reading gardens (community library) are one of the factors that can foster an interest reading in children. The low interest in reading in children is on of the obstacles to the lack of desire and willingness of children to read. In an effort to foster an interest in reading in children, a student helped by establishing a reading garden in a village, Pelawan distric, Sarolangun distric. Learning to read will not achieve satisfactory result for children if it is only carried out by reading. Textbooks only provide specific, narrow, and limited experience in certain fielsd or subjects. While children in their development really need broader experiences so they can see further into their world. Therefore, students prepare or provide places and books that suit the needs of children’s reading interest. In this case, the reading garden has a strategic role, especially in supporting efforts to build a childern’s reading culture. For that, reading gardens must be managedso that they are able to support efforts to foster children’s reading interests and awareness that books are a source of knowledge.